2015
DOI: 10.13005/ojc/320226
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Spectroscopy Study of the AC Conductivity and Dielectric properties of 3, 5-Dimethylpyridine-Iodine Charge Transfer Complex

Abstract: Solid charge transfer complex of n-donor 3, 5-dimethylpyridine (3, 5-Lutidine) with s acceptor iodine was prepared and characterised by using elemental analysis, UV-Vis, FTIR, 1 H NMR spectroscopy and powder XRD techniques. The electrical parameters of the prepared complex in the pellet form were studied at various temperatures and at wide frequency range by employing AC complex impedance spectroscopic technique. The Nyquist (cole-cole) plots have been successfully explained by employing (RC)(RC)(RC) equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The complex permittivity ε*(ω) is known as ε*(ω) = ε′(ω) − jε″(ω) [20], in which the real part Nyquist plot is due to the superposition of three contributions. In other word three distinct semicircular arcs are not observed; one corresponds to the grain resistance contribution located at high frequency RC element; the medium corresponds to grain boundary resistance and the low is associated to electrode contributions [13].…”
Section: Dielectric Permittivitymentioning
confidence: 92%
“…The complex permittivity ε*(ω) is known as ε*(ω) = ε′(ω) − jε″(ω) [20], in which the real part Nyquist plot is due to the superposition of three contributions. In other word three distinct semicircular arcs are not observed; one corresponds to the grain resistance contribution located at high frequency RC element; the medium corresponds to grain boundary resistance and the low is associated to electrode contributions [13].…”
Section: Dielectric Permittivitymentioning
confidence: 92%
“…[ 19 ] Furthermore, a band at 854 cm −1 was discernible after antibody immobilization, this band has been assigned to C‐H torsion due to the amino acid residues added with the antibody. [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…[19] Furthermore, a band at 854 cm −1 was discernible after antibody immobilization, this band has been assigned to C-H torsion due to the amino acid residues added with the antibody. [20] The process of antibody immobilization on CNC-Ch also increased the hydrodynamic radius of the CNCs. When the chitosan was adsorbed on the surface, the particles more than doubled their size, and the zeta potential changed from −10.4 ± 2.7 mV to 65.9 ± 0.97 mV which indicated colloidal stability.…”
Section: Antibody Immobilization Onto Cnc-chmentioning
confidence: 99%
“…3a shows the variation of a.c impedance, Z with logarithamic frequency for PAB-30%, 40%&50% composites at room tempera-ture. It is observed that, Z values decreases with increase in frequen-cy and at higher frequencies the values of Z merges beyond the fre-quency 5.8 Hz for all the wt% of the composites, this may be due to the polarization effect [ 20,21].…”
Section: Thermal Studiesmentioning
confidence: 88%